2004
DOI: 10.1100/tsw.2004.188
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal Sinus of the Glans Penis Associated withActinomycesCase Reports and Review of Literature

Abstract: Pilonidal sinus is a well-recognized condition that occurs most commonly in the sacrococcygeal area of younger men. It is hypothesized to be an acquired chronic inflammation condition due mainly to hair trapped beneath the surface. A pilonidal sinus in the sacrococcygeal region is associated with recurrent infection, abscess formation, cellulitis, fistulae, and rarely, squamous cell carcinoma. A pilonidal sinus of the penis is a rare entity. The association of a penile pilonidal cyst and Actinomyces is even mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
3
19
0
1
Order By: Relevance
“…Few similar cases were found to be reported in the recent literature as rare incidences. Al Chalabi et al 4 reported a 24-year-old man with severe mental illness with a year history of recurrent ulcerating round lump on the penile shaft 5. Two other cases were reported by Chikkamuniyappa et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Few similar cases were found to be reported in the recent literature as rare incidences. Al Chalabi et al 4 reported a 24-year-old man with severe mental illness with a year history of recurrent ulcerating round lump on the penile shaft 5. Two other cases were reported by Chikkamuniyappa et al .…”
Section: Discussionmentioning
confidence: 97%
“…A sinus will then form to drain the suppuration. In the penis, although rare, the theory of formation is that the coronal sulcus acts as a cleft where the hair accumulates and is pushed into the shaft of the penis by mechanical force between the prepuce and glans penis 1 4…”
Section: Discussionmentioning
confidence: 99%
“…The same condition can be seen in the clefts between fingers in those persons dealing with hair such as barbers and hairdressers (6,7). It has been reported in other areas such as the umbilicus (8)(9)(10), the interdigital spaces of the foot (11), the finger pulp (12), the clitoris (13,14), penis (15)(16)(17), the intermammary (18), the periungual (19) and the perineal regions (20).…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, septic arthritis was reported in a patient with rheumatoid arthritis after the resection of PNS (32). Although Actinomycosis associated with PNS of the penis is extremely rare, few cases have been reported (16,17,33). Neglected PNS can lead to unusual and life-threatening consequences.…”
Section: Pns Complicationsmentioning
confidence: 99%
“…Pilonidal sinus is a well‐recognised condition that occurs most commonly in the sacrococcygeal area of younger men. It is hypothesised to be an acquired chronic inflammation mainly because of hair trapped beneath the surface (1). The infection is usually chronic and non specific (2).…”
Section: Introductionmentioning
confidence: 99%